The effects of fluorine on the structural, surface morphology and optical properties of ZnO thin films - Yakuphanoğlu, Fahrettin; Caglar, Yasemin; Ilican, Saliha; Caglar, Muidat (Elsevier, 2007)
The optical and structural properties of fluorine-doped Zinc oxide (ZnO) thin films have been investigated. The X-ray diffraction spectra indicate that the films have polycrystalline nature. A ZnO single phase with a hexagonal wurtzite structure was observed in structure of the films. The grain size for the films was calculated using a well-known Scherrer's formula and the obtained values are in the range of 27-40 nm. The values of direct band gap E-g(d) were determined and these values change with doped fluorine (F) content. The shift of absorption edge is associated with Burstein-Moss effect. The width of localized states in the optical band of the films change with F content and the E-U values change inversely with optical band gap values of the films. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: thin film; optical band gap; ZnO; optical constant